(untitled) (Advancements in Homeopathic Research, 2022)
Objective:The study was conducted to elicit the pathogenetic response of Zingiber officinalis in homoeopathic potency 30C on healthy human volunteers. Methodology:The drug Zingiber Officinalis was reproved in Vinayaka Mission Homoeopathic Medical College and Hospital through randomized, double-blind, placebo-controlled method. The proving was conducted in the Department of Homoeopathic pharmacy, Vinayaka Mission’s Homoeopathic Medical College and Hospital Salem. The drug was proved in 30th centesimal potency on 36 apparently healthy volunteers who were selected after conducting pre trial medical examinations by the medical specialists and routine laboratory investigations. 18 of them were kept on interventional drug trial and remaining, under placebo. As per the proving protocol, 56 dose schedule [i.e., 56 doses of drug/placebo were consumed by a prover in each batch] was followed while at drug proving in Vinayaka Missions Homoeopathic Medical College and Hospital. The symptoms generated during the trial period were noted by the volunteers and elaborated by the proving masters which were compiled at Homoeopathic drug proving cum data processing unit of Homoeopathic Pharmacy Vinayaka Missions Homoeopathic Medical College and Hospital. Result:Out of 18 provers who were on the interventional drug trial, only 16 manifested symptoms. The drug was able to produce symptoms in 30C potencies, 17 symptoms appeared during proving in Vinayaka Mission Homoeopathic Medical College & Hospital. Conclusion:The drug pathogenesis evolved indicate its therapeutic use for migraine, acute rhinitis, gastritis, APD, ulcerative colitis and diarrheal conditions, urethritis, laryngitis, lower respiratory tract infections, etc.